2014
DOI: 10.1016/j.pharep.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin inhibits growth and alters the malignant phenotype of the C6 glioma cell line

Abstract: The inhibitory effects of fluvastatin on cell proliferation seemed to be associated with decreased p-ERK1/2 expression, upregulation of p-JNK1/2, and reduction in the MMP-9 and VEGF concentrations in culture media. The high anticancer (antiproliferative, proapoptotic, antiinvasive) activity of fluvastatin and lack of its toxicity against normal cells indicate a potential use of this statin in the treatment of malignant glioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…SIM exerted more cytotoxic effect than ATOR due to the difference in pharmacokinetic properties especially lipophilicity. Sławińska-Brych A et al (2014) reported the IC50 of SIM on MCF7 and MDM-231 ranging 1.26 to 91 µM and different with other cancerous cells [20] . The cytotoxicity of SIM and ATOR and DOX were measured by MTT.…”
Section: Discussionmentioning
confidence: 99%
“…SIM exerted more cytotoxic effect than ATOR due to the difference in pharmacokinetic properties especially lipophilicity. Sławińska-Brych A et al (2014) reported the IC50 of SIM on MCF7 and MDM-231 ranging 1.26 to 91 µM and different with other cancerous cells [20] . The cytotoxicity of SIM and ATOR and DOX were measured by MTT.…”
Section: Discussionmentioning
confidence: 99%
“…Statins are inhibitors of 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGCR), which is the rate-limiting enzyme in the melavonate pathway; a pathway producing a range of cell signalling molecules with the potential to regulate oncogenesis. This is supported by strong laboratory evidence that statins induce anticarcinogenic effects on cell proliferation and survival in various cell lines [1][2][3][4] , and reduce tumour growth in a range of in vivo models [5][6][7][8][9][10] .…”
mentioning
confidence: 82%
“…In addition to its cholesterol-lowering activities, fluvastatin has selective anti-cancer effects, such as the induction of tumor cell apoptosis in specific cancer cell lines (e.g., glioma and breast cancer cell lines) [5, 6]. Fluvastatin has also been suggested to have therapeutic potential for the treatment of HCC [7].…”
Section: Introductionmentioning
confidence: 99%